Huoxue Qianyang Qutan recipe attenuates cardiac fibrosis by inhibiting the NLRP3 inflammasome signalling pathway in obese hypertensive rats - Bo Lu; Jun Xie; Deyu Fu; Xiaozhe Chen; Mingyi Zhao; Mingtai Gui; Lei Yao; Xunjie Zhou; Jianhua Li (Taylor & Francis Group, 2021)
Context HuoXue QianYang QuTan Recipe (HQQR) is used to manage hypertension and cardiac remodelling, but the mechanism is elusive. Objective To determine the mechanism of HQQR on obesity hypertension (OBH)-related myocardial fibrosis. Materials and methods OBH models were prepared using spontaneously hypertensive rats (SHRs) and divided (n = 6) into saline, low-dose (19.35 g/kg/d) HQQR, high-dose (38.7 g/kg/d) HQQR, and valsartan (30 mg/kg/d) groups for 10 weeks. Systolic blood pressure (SBP), and Lee's index were measured. Heart tissues were examined by histology. HQQR's effects were examined on cardiac fibroblasts (CFs) stimulated with angiotensin II and treated with HQQR, a caspase-1 inhibitor, siNLRP3, and oeNLRP3. Results HQQR(H) reduced SBP (201.67 ± 21.00 vs. 169.00 ± 10.00), Lee's index (321.50 ± 3.87 vs. 314.58 ± 3.88), and left ventricle mass index (3.26 ± 0.27 vs. 2.71 ± 0.12) in vivo. HQQR reduced percentage of fibrosis area (18.99 ± 3.90 vs. 13.37 ± 3.39), IL-1β (10.07 ± 1.16 vs. 5.35 ± 1.29), and inhibited activation of NLRP3/caspase-1/IL-1β pathway. HQQR also inhibiting the proliferation (1.09 ± 0.02 vs. 0.84 ± 0.01), fibroblast to myofibroblast transition (14.74 ± 3.39 vs. 3.97 ± 0.53), and collagen deposition (Col I; 0.50 ± 0.02 vs. 0.27 ± 0.05 and Col III; 0.48 ± 0.21 vs. 0.26 ± 0.11) with different concentrations selected based on IC50 in vitro (all ps < 0.05). NLRP3 interference further confirmed HQQR inhibiting NLRP3 inflammasome signalling. Conclusion HQQR blunted cardiac fibrosis development in OBH and suppressed CFs proliferation by directly interfering with the NLRP3/caspase-1/IL-1β pathway.